A Trait‐like Component of Subjective Memory Concern in Men from Average Age 38 to 67 Years. (20th December 2022) - Bell, Tyler Reed; Beck, Asad; Franz, Carol E; Gillespie, Nathan A.; Reynolds, Chandra A.; Williams, McKenna E.; Kremen, William S.
Abstract: Background: Subjective memory concern is a risk factor for dementia in older adults, yet it also appears to be stable over time. Few studies examine memory concern starting in midlife in cognitively normal adults or the role of genetic influences on memory concern. We focused on the stability of subjective memory concern from early midlife into older adulthood and its association with objectively assessed episodic memory and depressive symptoms. Using a classical twin design, we assessed genetic and environmental influences on longitudinally‐assessed subjective concern and its overlap with episodic memory and depressive symptoms. Method: We examined 1, 334 community‐dwelling men assessed in the Survey of Health and the Vietnam Era Twin Study of Aging, who were assessed for subjective memory concern at average ages 38, 56, 62, and 67. Objective episodic memory and depressive symptoms were assessed at 56, 62, and 67. Biometric twin models were used to estimate genetic and environmental influences over time, and correlated genetic and environmental influences between measures. Result: Subjective memory concern was highly stable after average age 38 and not significantly associated with age. Phenotypic models showed that subjective memory concern was more related to depressive symptoms (β = .46) than with episodic memory (β = ‐.12) within timepoint, as shown by non‐overlapping confidence intervals. There were no significant lagged associations of subjective memory concern with episodic memory or depressive symptoms. Heritability of subjective memory concern was 51% and remained stable over time; 49% of the variation was attributed to unshared environmental influences. There were also significant genetic correlations between subjective memory concern and both episodic memory and depressive symptoms. Conclusion: Subjective memory concern was stable from age 38 to age 67, and over half of the variance was explained by genetic influences. There was also significant genetic overlap with depressive symptoms and episodic memory. The stability and heritability results provide strong support for a trait‐like component of subjective memory concern. To be most useful as an indicator of imminent cognitive decline and increased risk for dementia, it will be important to differentiate dynamic aspects of subjective concern from its trait‐related dimension.